UTILIZATION OF ARDUINO-BASED BLUETOOTH CONNECTION FOR ELECTRONIC EQUIPMENT CONTROL WITH VOICE COMMANDS - Hafdiarsya Saiyar (Kresnamedia Publisher, 2021)
Electronic equipment is a daily necessity in human life, but not infrequently we use electronic equipment excessively or ineffectively and the main problem is the factor of forgetting and being lazy to turn off electronic equipment. This makes wasteful use of electricity so that the costs charged are greater and there is the greatest risk of contact currents causing fire if we neglect to use lighting. Therefore, the author tries to make a control device for electronic equipment with voice commands connected to Bluetooth on a smartphone so that users can give commands to activate or deactivate electronic equipment with voice commands. The research method used is direct observation of the selected object, namely the author's house, and conducting literature studies related to the Arduino microcontroller. The Arduino microcontroller acts as the main controller connected to the relay module and the relay module connected to the power plug. In addition, Arduino is also connected to Bluetooth as a place to process incoming commands. The purpose of this research is to produce a tool that can make it easier to turn on or turn off electronic equipment with voice commands via an Android smartphone by utilizing an Arduino-based Bluetooth connection.